Texas Ranger [compact disc, unabridged] - Patterson, James, 1947-; Bourelle, Andrew (Hachette Audio, 2018)
Dedicated Texas Ranger Rory Yates is wrongly implicated in the murder of his ex-wife and finds his skills pushed to the limit in his effort to discover the real killer and prove his own innocence.